A new and environmentally benign synthesis of aroylguanidines using iron trichloride. Issue 123 (25th November 2015) - Pape, Simon; Wessig, Pablo; Brunner, Heiko
Abstract : A new synthetic approach for the guanylation of aroylthioureas using iron trichloride is presented. Abstract : A new synthetic approach for the guanylation of aroylthioureas using iron trichloride is presented. Our synthetic method distinguishes itself by benign reaction conditions, low costs and a broad product spectrum. The scope of the reaction and calorimetric studies are described.